Uncalibrated pulse power analysis fails to reliably measure cardiac output in patients undergoing coronary artery bypass surgery - Broch, Ole (BioMed Central, 2011)
INTRODUCTION: Uncalibrated arterial pulse power analysis has been recently introduced for continuous monitoring of cardiac index (CI). The aim of the present study was to compare the accuracy of arterial pulse power analysis with intermittent transpulmonary thermodilution (TPTD) before and after cardiopulmonary bypass (CPB). METHODS: Forty-two patients scheduled for elective coronary surgery were studied after induction of anaesthesia, before and after CPB respectively. Each patient was monitored with the pulse contour cardiac output (PiCCO) system, a central venous line and the recently introduced LiDCO monitoring system. Haemodynamic variables included measurement of CI derived by transpulmonary thermodilution (CI(TPTD)) or CI derived by pulse power analysis (CI(PP)), before and after calibration (CI(PPnon-cal.), CI(PPcal.)). Percentage changes of CI (ΔCI(TPTD), ΔCI(PPnon-cal./PPcal.)) were calculated to analyse directional changes. RESULTS: Before CPB there was no significant correlation between CI(PPnon-cal. )and CI(TPTD )(r(2 )= 0.04, P = 0.08) with a percentage error (PE) of 86%. Higher mean arterial pressure (MAP) values were significantly correlated with higher CI(PPnon-cal. )(r(2 )= 0.26, P < 0.0001). After CPB, CI(PPcal. )revealed a significant correlation compared with CI(TPTD )(r(2 )= 0.77, P < 0.0001) with PE of 28%. Changes in CI(PPcal. )(ΔCI(PPcal.)) showed a correlation with changes in CI(TPTD )(ΔCI(TPTD)) only after CPB (r(2 )= 0.52, P = 0.005). CONCLUSIONS: Uncalibrated pulse power analysis was significantly influenced by MAP and was not able to reliably measure CI compared with TPTD. Calibration improved accuracy, but pulse power analysis was still not consistently interchangeable with TPTD. Only calibrated pulse power analysis was able to reliably track haemodynamic changes and trends.